Comparative evaluation of the effectiveness of 2 and 3D visualizations in students' understanding of structures of organic molecules - Oke, O.K.; Alam, G.M. (Academic Journals, 2010)
Adopting quantitative approach using test as a key instrument, this study investigated the relative effectiveness of 2 and 3D visualizations on students' performance in the study of organic molecules, structures and nomenclature. The instrument was administered before and after treating two experimental groups with 2 and 3D supplemental learning software following a conventional teaching. The control group was made to interact with textbooks at the times the experimental groups were in the computer laboratory viewing the CD-ROMs. The study was conducted at a College in Lagos. The College had 205 chemistry students and of 205, 40% were randomly selected as the study sample. They were in turn randomly assigned to the three groups. Findings show that due to cultural and economical prejudice and long heritage of traditional teaching, assessment and learning system in place, many students are familiar with traditional system and they also feel comfortable with it. This is why the performance of the group making use of 2D visualization significantly better than the other group making use of 3D visualization. However, scores of students in both experimental groups were close which is higher than control group. Moreover, it is evident that the use of 2 and 3D visualizations enhanced performance in organic chemistry and thus one supplements other. Considering these, the simultaneous use of the two visualizations in the teaching and learning of organic molecules and structures based on closeness of the mean scores of the two experimental groups is suggested considering that 3D might prove more enhancing if students get used to it.